PENGARUHMBELAJARAN DARING TERHADAP HASIL BELAJAR MATEMATIKA PADA MASA PANDEMI DI SMA NUSANTARA INDAH SINTANG - Andri, Andri; Romet, Wenseslaus Tiobala (Kadikma, 2021)
The purpose of this study was to determine the effect of online learning on mathematics learning outcomes during the pandemic at SMA Nusantara Indah Sintang. The research approach used is a quantitative approach with regression research methods and simple regression research forms. The results of the F test or the significance value test (Sig.) obtained the value of Sig. = 0.067 which means > significant criteria (0.05), thus the regression equation model based on research data is not significant, as well as the results of the t test. There is a significant relationship between online learning and the learning outcomes of SMA Nusantara Indah Sintang students